Construction of Moral Messages in One Piece Animation on Netflix Streaming Television Media (A Case Study of Students at SMA Negeri 9 Bandar Lampung) - Rahmat Fauzan Yaqdhan; Wawan Hernawan; Hanindyalaila Pienrasmi (CONVERSE Journal Communication Science, 2025)
This study aims to examine the construction of moral messages in the Netflix adaptation of the One Piece animation and how these messages are received and interpreted by students at SMA Negeri 9 Bandar Lampung, like perspectives on life, friendship, justice, and courage. In the Netflix version, there is a possibility of meaning shifts in the moral messages due to cultural adaptation, global marketing strategies, and narrative interests of the production. This research employs a qualitative approach using a case study method. Data collection techniques include in-depth interviews, observation, and documentation involving selected student informants. Data analysis follows Miles and Huberman's interactive model, consisting of data reduction, data display, and conclusion drawing